Ileocolic intussusception caused by a submucosal ileal lipoma in a teenager: A case report - Aliou Zabeirou; Boubacar Efared; Mahamoud Oumid Ali Ada; Djamila Soli abdourahmane; Adama Saidou; Idrissa Boubacar; James Didier Lassey; Rachid Sani (Elsevier, 2023)
Introduction: Intussusception is a rare condition in adolescents; its incidence is highest between three months and three years of age. The symptoms of intussusception are abdominal pain and bowel obstruction. Organic origin is the most common etiology of intestinal intussusception in adolescents, unlike pediatric intussusception, which is usually idiopathic. Adolescent intussusception due to ileal submucosal lipoma is infrequent, and only a few cases have been reported in the medical literature. Case presentation: A 14-year-old female patient was admitted to the emergency department with abdominal pain, nausea, and bilious vomiting. She had no significant medical history. The abdominal examination revealed typical signs of acute bowel obstruction. An enhanced abdominal CT scan showed an invagination of the distal ileal loop within the ascending colon lumen with a rounded fat aspect. Emergency laparoscopic-assisted right hemicolectomy and ileocolic anastomosis were performed. The patient recovered well and was discharged three days after surgery. Histological examination of the surgical specimen confirmed the diagnosis of intussusception due to an ileal submucosal lipoma. Conclusion: The symptoms of bowel intussusception due to an ileal submucosal lipoma in adolescents are similar to any other bowel intussusception due to other etiologies. A contrast-enhanced abdominopelvic CT scan and histopathological analysis are valuable techniques to achieve the correct diagnosis.